Why we need employees back at the office: The effect of workplace design on creativity in organizations - Zita K. Lucius; Svenja Damberg (Creativity and Innovation Management, 2024)
With the ongoing changes in the work environment, specifically turning from fulltime to no time at the office and nowadays pending somewhere in between, there is a need for decision makers to redefine their expectations of a day at the office. Previously, organizations worldwide focussed on creating workplaces that foster interaction and collaboration to enhance knowledge exchange and communication. Both are among the main drivers for stimulating creativity at the workplace, leading to increased innovation activities. Since offices are dramatically changing from lean, work-focused, and hierarchical workstations into employee-oriented, creativity-enhancing spaces with playground artefacts, the need for quantitative research on the effects of workplace design on creativity seems evident for researchers and practitioners. Although prior research has attempted to describe the physical work environment and its impact on creativity, empirical evidence is still lacking on what concrete attributes of a workplace employees perceive as inspiring. We therefore contribute to the existent body of knowledge by establishing a definition for inspiring physical workplaces as perceived by employees in times of digitalization and provide a conceptual model analysing the effects between workplace design, internal knowledge exchange, and creative problem-solving capacity. We assess our survey data with partial least squares structural equation modelling and provide first empirical evidence that our proposed formative index supports the common research agenda within the context of workplace design, and further, that aspects of workplace design not only enhance creative problem-solving capacity as an important dimension of creativity itself, but that this relationship is also partially mediated by internal knowledge exchange.
Keywords: 330; creative problem-solving capacity; internal knowledge exchange; new work; PLS-SEM; working from home; workplace design